Military pay systems analysis of some NATO member countries - Chimyshenko, S. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The article examines the military pay services of some NATO member countries in the context of applying the experience of these countries to reform the military pay service of the Armed Forces of Ukraine and other military formations created under the current legislation. The focus is on the structure and principles of building these military pay services. The problems of the military pay services of the Armed Forces of Ukraine have become chronic and do not adequately reflect the achievements of servicemen during their military service. The low percentage of payment by military rank and position contradicts their appointment and their motivational role. Instead, the non-guaranteed part of military pay, which is intended to differentiate the sizes of military pay of specific servicemen depending on their level of skills and achievements in service, significantly outweighs in the total amount of accrued military pay. To overcome these shortcomings, the article identifies the main general principles of building military pay services of some NATO member countries, the main ones being the calculation of a unified (basic) payment and its dependence only on the military rank of servicemen. The identified principles provide simplicity and transparency of military pay services of the studied NATO member countries and ensure compliance of these systems with their stimulating role in the system of military service motivation. In addition, the military pay services of the studied NATO member countries ensure effective promotion and career advancement in the military. This, in turn, allows for the recruitment of the best servicemen and prevents the promotion of non-promising military personnel.